A protein-truncating R179X variant in RNF186 confers protection against ulcerative colitis - Manuel A. Rivas (Nature Portfolio, 2016)
While hundreds of loci are linked with inflammatory bowel diseases (IBDs), the functional consequences of the associated variants remain unclear. Here, the authors screened in ulcerative colitis (UC) patients’ genomes for protein-truncating variants near IBD loci, and identify a protein truncating variant in RNF186to be protective against UC.